2009
DOI: 10.5551/jat.509
|View full text |Cite
|
Sign up to set email alerts
|

A Reconstituted High Density Lipoprotein Containing the V156E Mutant of Apolipoprotein A-I Exhibits Anti-Atherosclerotic Activity in Apo-E Deficient Mice

Abstract: Aim: A point mutation of apolipoprotein A-, V156E, is naturally occurring and is found in Oita, Japan. V156E of apoA-(apoA-oita) shows unique structural and functional properties and more potent antioxidant activity against copper-mediated low-density lipoprotein (LDL) oxidation in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…Short term weekly infusions of reconstituted HDL particles resulted in rapid and significant regression of coronary atherosclerosis in patients with acute coronary syndrome [16]. Similar, though more striking, results have been obtained in apolipoprotein (apo) E knockout (KO) mice injected with reconstituted HDL [29], [30]. A study of atherosclerotic plaque regression in mice has reported significant alterations in the expression of a variety of genes in inflammatory cells in the regressing plaques, including significantly increased expression of the scavenger receptor class B, type I (SR-BI) [13].…”
Section: Introductionmentioning
confidence: 53%
“…Short term weekly infusions of reconstituted HDL particles resulted in rapid and significant regression of coronary atherosclerosis in patients with acute coronary syndrome [16]. Similar, though more striking, results have been obtained in apolipoprotein (apo) E knockout (KO) mice injected with reconstituted HDL [29], [30]. A study of atherosclerotic plaque regression in mice has reported significant alterations in the expression of a variety of genes in inflammatory cells in the regressing plaques, including significantly increased expression of the scavenger receptor class B, type I (SR-BI) [13].…”
Section: Introductionmentioning
confidence: 53%
“…Specifically, rHDL reduces the lipid content of atherosclerotic plaques and the accumulation of macrophages in the lesion area, increases serum PON1 activity and decreases circulating levels of lipid peroxidation products. Similarly, enhanced lesion regression activity paralleled by improved anti-inflammatory and antioxidative capacities are features of another point mutant of apoA-I, V156E that naturally occurs in Oita, Japan [96]. Similarly, enhanced lesion regression activity paralleled by improved anti-inflammatory and antioxidative capacities are features of another point mutant of apoA-I, V156E that naturally occurs in Oita, Japan [96].…”
Section: Effects On Hdl Functionalitymentioning
confidence: 93%
“…Various basic studies have been performed using recombinant HDL [apoA-I Milano (67), CER-001 (68)], apoA-I mimetic peptides (69), reconstituted HDL [rHDL (70), CSL-111 (71)], delipidated HDL (72), and antagonist of microRNA-33 (Anti-miR33) (73). ApoA-I mimetic peptides are a major example; the 5F peptide inhibits the formation of aortic plaque in mice receiving a high-fat diet, which is the first in vivo demonstration that apoA-I mimetic peptides have atheroprotective properties (74).…”
Section: High-density Lipoprotein (Hdl)mentioning
confidence: 99%